SUSTAINABILITY STATUS OF TRAP FISHERIES IN THE SOUTHERN PART OF RANGSANG ISLAND - Brown, Arthur; Simamora, Valentine Vanda; Yani, Alit Hindri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
On Rangsang Island, many still work as fishermen or depend on the sea, especially in the southern part of Rangsang Island. Fishermen in the south part of Rangsang Island still use a lot of traditional fishing gear, such as the grinder. The polluted waters on Rangsang Island and destructive technology will impact the fishermen's fishing economy. This study aims to determine and assess the sustainability of fishing gear in terms of ecological, economic, and technological aspects in the southern part of Rangsang Island using the rapfish technique. The method used was a survey method, and the sampling used a purposive sampling technique. The analysis of the rapfish technique found that sustainability in the ecological dimension was 33.53% or less sustainable. In the economic dimension, it was 36.01% or less sustainable. In comparison, it was 76.71% sustainable in the technological dimension.